Traumatic abdominal wall hernia with hemoperitoneum caused by blunt injury: laparoscopic exploration with mini-laparotomy repair. A case report - Euisung Jeong; Hyunseok Jang; Younggoun Jo; Yunchul Park; Naa Lee; Jungchul Kim (Journal of Trauma and Injury)
Traumatic abdominal wall hernia is a very rare clinical entity. Herein, we report the case of a patient who was transferred from a local clinic to the emergency department because of left lower abdominal pain. Initially, an intra-abdominal hematoma was observed on computed tomography and no extravasation was noted. Conservative treatment was initiated, and the patient’s symptoms were slightly relieved. However, though abdominal pain was relieved during the hospital stay, bowel herniation was suspected in the left periumbilical area. Follow-up computed tomography showed traumatic abdominal wall hernia with hemoperitoneum in the abdomen. We performed a laparoscopic exploration of the injury site and hernia lesion. The anterior abdominal wall hernia was successfully closed.